Using Flashcard-Based Techniques to Improve Students’ Vocabulary Retention (Journal of Contemporary Educational Policies and Practices, 2023)
The study aims to investigate how flashcard-based techniques are used to improve students’ vocabulary retention as well as the students’ perceptions and attitudes toward using flashcard-based techniques to improve vocabulary retention and the difficulties they faced during their learning process. The four-week study involved 18 students from an entire class at a language center. The data from vocabulary tests, questionnaires, student self-evaluation checklists, and students’ reflections were analyzed using both qualitative and quantitative methods. The test results and student reflections demonstrate that flashcard-based techniques contributed significantly to the students’ vocabulary recall. The findings of the survey, together with student self-evaluation checklists and their comments, reveal that these students had favourable perceptions and positive attitudes toward their vocabulary retention as a result of the teacher’s use of flashcard-based techniques. A variety of challenges during the learning process faced by the participants also offer meaningful suggestions for both the learners and teachers to effectively facilitate the former’s vocabulary retention.
Keywords: Vocabulary retention; flashcard-based technique; students; action research